SOCIAL-PSYCHOLOGICAL MECHANISMS IN INCLUSIVE EDUCATION ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
Inclusive education fosters an environment where students with diverse abilities learn together, promoting social integration and equality. This paper explores the social-psychological mechanisms that drive inclusive education, examining factors such as group dynamics, social identity, peer influence, and empathy development. Through both qualitative and quantitative methods, this study identifies key mechanisms that facilitate or hinder effective inclusion. Findings suggest that successful inclusive practices rely on understanding social interactions, fostering positive peer attitudes, and supporting teachers in managing diverse classrooms. Recommendations are provided to enhance the effectiveness of inclusive education through targeted social-psychological interventions.